RISK FACTORS CONTRIBUTING TO THE FORMATION OF THE SYSTEM OSTEOPOROSIS AND OSTEOPENIA IN DIFFUSE TOXIC GOITER - Герасименко, Л.В. (World of Medicine and Biology, 2015)
Two hundred and forty three patients with diffuse toxic goiter (DTG) were examined with the purpose to study the risk factors in formation of structural functional disorders of the osseous tissue, in particular, osteoporotic processes and evaluation of diagnostic value of radiomorphometric examinations and ultrasound densitometry. All examined patients were divided into three groups. The first group included females with diffuse toxic goiter while their reproductive period. The second group consisted of DTG female patients in menopause. The third group included male patients with thyrotoxicosis associated with diffuse goiter. The analysis of the correlations of ultrasonic bone densitometry indices, radiomorphometry of bones and parametres of sex, thyroid and calcitropic hormones was carried out to study the risk factors which favour formation of structural functional disorders of the bone tissue at DTG and to evaluate metabolism of the osseous tissue. The studied groups had statistically significant differences in the parametres of age, duration of the disease, levels of testosteron, estradiol, cortisol, metacarpal index, characteristics of ultrasound propagation speed, strength index and densitometry Т-score.Blood estradiol level and ultrasound densitometry parametres and radiomorphometry of the bones demonstrated feasible direct correlation in females both of reproductive age with metacarpal index and menopausal periods with strength index. Thus, the decrease of estradiol in the females of reproductive age will cause the loss of mineral density of the osseaus tissue, first of all in the bones of hands. In menopausal women the low estradiol level will increase the loss of mineral density of all skeletal osseous tissue, i.e. will cause systemic osteoporosis. It has been revealed that the elevation of cortisol level in blood of the patients with DTG leads to the decrease of mineral density of osseous tissue in axial skeleton both in menopausal women and men.The DTG patients showed significant inverse relation between the level of free triiodthyronin in blood and parametres of ultrasound bone densitometry in reproductive age females. But the control group of menopausal women gave the more impressive inverse relation between the level of free triiodthyronin and broadband ultrasound attenuation. No reliable relations between the level of calcitonin in blood and parameters of the ultrasound bone densitometry and radiomorphometry in the patients of the studied groups were revealed. The carried analysis revealed that the risk factors in the patients with DTG are the following: high levels of triiodthyronin and cortisol in blood, low level of estradiol, advanced age and great duration of the disease. The positive influence on the osseous tissue in the patients with DTG is given by the high level of osteocalcin, testosteron and free thyroxin in blood.
Keywords: osteoporosis; osteopenia; risk factors; hyperthyroidism